2021
DOI: 10.3390/plants10020308
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Acetyltransferase GCN5 and the Associated Coactivators ADA2: From Evolution of the SAGA Complex to the Biological Roles in Plants

Abstract: Transcription of protein-encoding genes starts with forming a pre-initiation complex comprised of RNA polymerase II and several general transcription factors. To activate gene expression, transcription factors must overcome repressive chromatin structure, which is accomplished with multiprotein complexes. One such complex, SAGA, modifies the nucleosomal histones through acetylation and other histone modifications. A prototypical histone acetyltransferase (HAT) known as general control non-repressed protein 5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…In comparison to yeast and other eukaryotes, Arabidopsis thaliana has two ADA3 genes, designated ADA3a and ADA3b. Other members of the yeast SAGA complex also have two orthologues in Arabidopsis thaliana, like ADA2a and ADA2b, as well as SGF29a and SGF29b [21]. ADA3 protein is vital for the development of other eukaryotes [8,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to yeast and other eukaryotes, Arabidopsis thaliana has two ADA3 genes, designated ADA3a and ADA3b. Other members of the yeast SAGA complex also have two orthologues in Arabidopsis thaliana, like ADA2a and ADA2b, as well as SGF29a and SGF29b [21]. ADA3 protein is vital for the development of other eukaryotes [8,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of Viridiplantae putative ADA3 proteins revealed that ADA3 is absent only in chlorophytes. The first appearance of ADA3 protein was observed in charophytes, such as Klebsormidium nitens and Chara braunii, followed by liverworts, mosses, and lycophytes, ANA clade, monocots, and eudicots (Figure 2) [21]. Searching for motifs in ADA3 polypeptide sequences in plant models, including Arabidopsis, Brachypodium, Amborella, Selaginella, Physcomitrella, and Marchantia indicated that the primary structure of the ADA3 proteins is highly conserved (Figure S4).…”
Section: The Arabidopsis Thaliana Genome Encodes Two Ada3 Homologuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify the upstream-regulatory events that controlled proteins in soybean root tips through plant-derived smoke solution, nuclear proteomic analysis was performed. Transcription of protein-encoding genes starts with forming a pre-initiation complex comprised of RNA polymerase II and several general transcription factors [31]. RNA polymerase II modifications play a critical biological function in fundamental cellular processes.…”
Section: The Effect Of Plant-derived Smoke Solution On Nucleus In Soybean Rootmentioning
confidence: 99%
“…In most cases, histone acetylation correlates with transcriptional activation, whereas histone methylation can activate or repress transcription, depending on the nature and position of lysine residues that are methylated ( Hu et al, 2015 ; Lämke et al, 2016 ; Liu et al, 2019 ; Sharma et al, 2019 ). Previous reports suggested the role of several chromatin remodelers and histone-modifying enzymes in the regulation of abiotic stress tolerance ( Singh et al, 2014 ; Weng et al, 2014 ; Hu et al, 2015 ; Zheng et al, 2019 ; Ueda and Seki, 2020 ; Vlachonasios et al, 2021 ). The enzymes HISTONE ACETYLTRANSFERASES (HATs) catalyse the acetylation of specific lysine residues (such as K9, K14, K18, K23, and K27) in the amino-terminal tail of histones, which are associated with the transcriptional activation of genes involved in different biological processes ( Boycheva et al, 2014 ; Shen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%